Benzothioxanthene Dicarboximide as a Tuneable Electrogenerated Chemiluminescence Dye. Issue 24 (11th November 2022) - Dauphin, Alice L.; Andrés Castán, José María; Yu, Jing; Blanchard, Philippe; Sojic, Neso; Ahn, Hyun S.; Walker, Bright; Cabanetos, Clément; Bouffier, Laurent
Abstract: Overlooked for years, the promising benzothioxanthene dicarboximide (BTXI) structure is nonetheless known to be an excellent fluorophore. As a further step towards the exploration of this rylene structure, the generation of electrochemiluminescence (ECL) in acetonitrile solutions is investigated herein as well as its direct comparison with a diphenylamine (DPA) derivative. Electrochemical characterization shows that the bare BTXI can be reversibly reduced or oxidized, characteristics which suggest the possibility that the electrogenerated reactive species can be exploited in the context of ECL. As a result, the BTXI moiety was found to be ECL‐active in both annihilation and co‐reactant mechanisms. Tri‐ n ‐propylamine (TPA) and benzoyl peroxide (BPO) were selected as sacrificial co‐reactants for promoting ECL. An ECL efficiency of 13 % (BTXI) and 6 % (BTXI‐DPA) compared to that of Ru(bpy)3 2+ was found when using TPA in oxidative ECL. Moreover, the ECL efficiency increased to 75 % and 55 % of Ru(bpy)3 2+ with BPO (i. e. reductive‐oxidation ECL) for BTXI and BTXI‐DPA, respectively. These results can be understood by calculating the free enthalpy of the redox reactions associated with each ECL pathway. Although the BTXI‐DPA red emitter exhibits more suitable thermodynamic properties, the BTXI green emitter is nonetheless more effective in combination with a co‐reactant due to a much larger photoluminescence quantum yield. The ECL spectra of the two molecules are compared to their photoluminescence spectra, revealing the involvement of the same excited states in the two different photoemission processes. In turn, the chemical engineering of BTXI is shown to be an effective platform for achieving tuneable ECL generation. Abstract : Electrogenerated Chemiluminescence Dye : Benzothioxanthene dicarboximide and a diphenylamine analogue are evaluated for the generation of electrochemiluminescence (ECL). The two molecules are found to be ECL‐active following the annihilation mode as well as co‐reactant mechanisms with an ECL efficiency of up to 75 % compared to a Ru(bpy)3 2+ standard.